British Standard on demolition (BS6187) Monday 16 November 1998, One Great George Street Conference Centre. (Thomas Telford, 1998)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in November 1998.